Analisis Penerapan Desain Biofilik Untuk Meningkatkan Produktivitas Ruang Bekerja Pada Industri Kreatif - Hanafi, Muhammad Hasan; Maharani, Rizka Tiara (Prodi Arsitektur Universitas Matana, 2024)
Creative industries have great potential and will continue to grow with the advancement of time. As a result, communities in the creative industries will continue to be formed, creating a space for collaboration that is contained in the creative workspace. The activities carried out in the workspace often require high productivity and creativity. If this is done continuously, it can lead to emotional and physical fatigue that can reduce work productivity. The solution to address this is to improve the comfort of working in the creative workspace environment with a biophilic approach in order to create a comfortable workspace that can improve productivity and creativity while working. This study aims to conduct a study of literature and journals that discuss biophilic design in the workplace that has an impact on the performance of creative industry actors. The research method chosen for this study is short communication by filtering journals and taking keywords